Design of High-Energy-Density fuels based on COSMO-RS - Jinxia Fu; Scott Q. Turn (Fuel, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

P30-60 Grouping and assessment of chemicals for hazard and risk assessment by high content analysis using the zebrafish embryos as an alternative non-sentient animal model - S. Scholz; C. Zanini; A.-K. Koblitz; T. Möller; M.A. Aslam; G.C. Ajugwo; E. Chukwu; J. Colbourne; S. Kader; Q. Fu; N. Grasse; T. Reemtsma; et al. (Toxicology Letters, 2025)

P30-57 Towards a Defined Approach to Assess Pesticides for their Potential to Cause Parkinsonian Neurodegeneration - J. Nyffeler; T. Tal; S. Schildknecht; B. Viviani; B. Tanja; Q. Fu; R. Owen; A.E.V. Krishnakumar; I. Mangas; A. Terron (Toxicology Letters, 2025)

P28-07 Investigating Placental Barrier Integrity Under Exposure to a Real-Life PFAS Mixture - V.M. Mailaender; S. Gomez-Olarte; Q. Fu; V. Stojanovska; N. Meyer; A.C. Zenclussen (Toxicology Letters, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Increasing humification and reducing CH4 emission during rice straw fermentation: the role of Streptomyces rochei ZY-2 - B. Fu; B. Gao; J. Zhang; H. Huang; Z. Wei; Q. Wang; P. Qu (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Oxidation mechanism of sulfur-containing compounds and antioxidant depletion dynamics: Insights into interactions - Jinxia Fu; Scott Q. Turn (Fuel, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P10-08 Evaluation of real-life PFAS mixture toxicity and impact on 3D placenta spheroid model - Y. Xia; Q. Fu; H. Voss; S. Fest; A.C. Zenclussen; V. Stojanovska (Toxicology Letters, 2024)

Nanocrystalline cellulose production from unbleached Ceiba pentandra (L.) Gaertn (Kapok) seed pod fibres via multiple acid hydrolysis: ‘More is Less’ or ‘Less is More’? - Abdulsalam Q. Almashhadani; Cheu Peng Leh; Choon Fu Goh (Biomass and Bioenergy, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Preparation of carbonaceous adsorption composite with refinery sludge for butyl xanthate and diethyldithiocarbamate removal in flotation wastewater - P. Fu; H. Yang; Q. Zhang; X. Li (International Journal of Environmental Science and Technology, 2023)

Data-driven ESG assessment for blockchain services: A comparative study in textiles and apparel industry - Xinlai Liu; Yu Yang; Yishuo Jiang; Yelin Fu; Ray Y. Zhong; Ming Li; George Q. Huang (Resources, Conservation and Recycling, 2023)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Methylated Unsymmetric BODIPY Compounds: Synthesis, High Fluorescence Quantum Yield and Long Fluorescence Time - Xian-Fu Zhang; George Q. Zhang; Jiale Zhu (Journal of Fluorescence, 2019)

Analysis of the Spatial Variation and Identification of Factors Affecting the Water Resources Carrying Capacity Based on the Cloud Model - K. Cheng; Q. Fu; J. Meng; T. X. Li; W. Pei (Water Resources Management, 2018)

A cardioid oscillator with asymmetric time ratio for establishing CPG models - Q. Fu; D. H. Wang; L. Xu; G. Yuan (Biological Cybernetics, 2018)

Effects of rate and application method on the efficacy of metam sodium to reduce clubroot (Plasmodiophora brassicae) of canola - S. F. Hwang; H. U. Ahmed; S. E. Strelkov; Q. Zhou; B. D. Gossen; G. Peng; G. D. Turnbull; H. Fu (European Journal of Plant Pathology, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Effects of Dietary Selenium Against Lead Toxicity on mRNA Levels of 25 Selenoprotein Genes in the Cartilage Tissue of Broiler Chicken - H Gao; C. P. Liu; S. Q. Song; J. Fu (Biological Trace Element Research, 2016)

Oncogenic and tumor suppressive roles of microRNAs in apoptosis and autophagy - Y. Chen; L. L. Fu; X. Wen; B. Liu; J. Huang; J. H. Wang; Y. Q. Wei (Apoptosis, 2014)

Influence of outbreak of macroalgal blooms on phosphorus release from the sediments in Swan Lake Wetland, China - L. Gao; Q. Wei; F. Fu; H. Shao (Plant Biosystems, 2013)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

Sequence organization and evolutionary dynamics of Brachypodium-specific centromere retrotransposons - L. L. Qi; J. J. Wu; B. Friebe; C. Qian; Y. Q. Gu; D. L. Fu; B. S. Gill (Chromosome Research, 2013)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impacts of cascade run-of-river dams on benthic diatoms in the Xiangxi River, China - N. Wu; T. Tang; X. Fu; W. Jiang; F. Li; S. Zhou; Q. Cai; N. Fohrer (Aquatic Sciences, 2010)

Differential expression of candidate genes for lignin biosynthesis under drought stress in maize leaves - Y. Hu; W. Ch. Li; Y. Q. Xu; G. J. Li; Y. Liao; F. -L. Fu (Journal of Applied Genetics, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Phylogeographical analysis of an estuarine fish, Salanx ariakensis (Osmeridae: Salanginae) in the north‐western Pacific - X. Hua; W. Wang; W. Yin; Q. He; B. Jin; J. Li; J. Chen; C. Fu (Journal of Fish Biology, 2009)
This study extended the geographic coverage of a previous study to explore population genetic structure and demographic history in the Ariake icefish Salanx ariakensis from three populations of continental coastlines and one island population in the north‐western Pacific based on a partial sequence of the mitochondrial cytochrome b gene. The S. ariakensis showed high genetic diversity and strong genetic structure. Phylogenetic analysis showed a shallow gene tree with no clear phylogeographical structure. Contiguous range expansion and restricted gene flow were inferred to be main population events by nested‐clade analysis. Significant genetic differentiations between populations could be attributable to negligible gene flow by coalescent analysis. High nucleotide diversity of each population was due to geographic mixing of heterogenous haplotypes during lowering sea levels of the Pleistocene. These findings indicate that cycles of geographic isolation and secondary contact happened in the Pleistocene glacial–interglacial cycles shaping genetic structure and population demography of S. ariakensis .

Simple menaquinones reduce carbon tetrachloride and iron (III) - Q. Shiang Fu; Benjaporn Boonchayaanant; Weiping Tang; Barry M. Trost; Craig S. Criddle (Biodegradation, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Floral biology of Nuphar pumila (Timm) DC. (Nymphaeaceae) in China - Q. Zhou; D. Fu (Plant Systematics and Evolution, 2007)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Genetic analyses and mapping of a new thermo-sensitive genic male sterile gene in maize - J. H. Tang; Z. Y. Fu; Y. M. Hu; J. S. Li; L. L. Sun; H. Q. Ji (Theoretical and Applied Genetics, 2006)

Removal of Cu2+ and dye from wastewater using the heavy metal precipitant N,N-bis-(dithiocarboxy)piperazine - F. L. Fu; Q. R. Xuan; R. M. Chen; Y. Xiong (Environmental Chemistry Letters, 2006)

Mercury Accumulation and Distribution in Medaka after the Exposure to Sublethal Levels of Methylmercury - C.-Y. Liao; Q.-F. Zhou; J.-B. Shi; J.-J. Fu; G.-B. Jiang (Bulletin of Environmental Contamination and Toxicology, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Analyses of cis -acting elements that affect the transposition of Mos1 mariner transposons in vivo - D. W. Pledger; Y. Q. Fu; C. J. Coates (Molecular Genetics and Genomics, 2004)

Microbial biomass carbon, nitrogen and phosphorus in the soil profiles of different vegetation covers established for soil rehabilitation in a red soil region of southeastern China - F.E. Wang; Y.X. Chen; G.M. Tian; S. Kumar; Y.F. He; Q.L. Fu; Q. Lin (Nutrient Cycling in Agroecosystems, 2004)

Three-dimensional organization and dynamic changes of the actin cytoskeleton in embryo sacs ofZea mays andTorenia fournieri - B. -Q. Huang; Y. Fu; S. Y. Zee; P. K. Hepler (Protoplasma, 1999)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)